2010
DOI: 10.1590/s1517-83822010000200021
|View full text |Cite
|
Sign up to set email alerts
|

Structure and composition of bacterial and fungal community in soil under soybean monoculture in the Brazilian Cerrado

Abstract: Soybean is the most important oilseed cultivated in the world and Brazil is the second major producer.Expansion of soybean cultivation has direct and indirect impacts on natural habitats of high conservation value, such as the Brazilian savannas (Cerrado). In addition to deforestation, land conversion includes the use of fertilizers and pesticides and can lead to changes in the soil microbial communities. This study evaluated the soil bacterial and fungal communities and the microbial biomass C in a native Cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 12 publications
1
19
1
7
Order By: Relevance
“…The properties affect the native microbial populations (Bresolin et al, 2010). This study showed small amounts of aluminum in the Amazon soil (Table 3).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The properties affect the native microbial populations (Bresolin et al, 2010). This study showed small amounts of aluminum in the Amazon soil (Table 3).…”
Section: Discussionmentioning
confidence: 69%
“…The large variability is due the incorporating of different types and quantities of organic matter (Bissett et al, 2013). Recently, Bresolin et al (2010) observed microbiota present in Brazilian Cerrado soil using DNA analysis by PCR-DGGE. The microbial species isolated were related to Uncultured soil fungus and Uncultured soil bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Diferenças entre as comunidades bacterianas de solo sob vegetação nativa e sob cultivo também foram relatadas por outros autores em solos de cerrado, em Santo Antônio de Goiás, GO (Peixoto et al, 2006), Cristalina, GO (Bresolin et al, 2010) e Planaltina, DF (Peixoto et al, 2010). Segundo Garbeva et al (2004), isso ocorre porque a estrutura das comunidades microbianas é afetada pela estrutura e pela composição da vegetação de cobertura, em virtude da liberação de formas específicas de carbono que podem representar importantes fontes de energia.…”
Section: Resultsunclassified
“…Microorganisms are essential components of ecosystems that participate in 80 to 90% of soil processes, such as the carbon and nitrogen biogeochemical cycles, and are efficient and dynamic indicators of soil quality (Bresolin et al, 2010). Different types of soils and plants possess specific microbial communities, and each plant species is colonized by a different microbial population that is mostly controlled by edaphic variables, especially pH (Berg and Smalla, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These new techniques are able to analyze the high complexity of microbial communities, especially because a minority of microbial groups cannot be grown in vitro (Bresolin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%